STUDI KRITIK TERHADAP BUKU â€œAGENDA PSIKOLOGI ISLAMIâ€ - Suciati Suciati (Universitas Ahmad Dahlan, 2014)
West is always grounded in empirical reality invites a number of intriguing questions, what about the non-empirical reality. Is not the reality that there is as it says in the Qur'an that genie natural and supernatural realm exists, it is not possible to study and produce a useful theory for the benefit of the people? Or whether people recognize the truth of non-empirical or metaphysical as a scientific truth that can be accounted for? Is actually a series of questions can be summarized into the question of: How epistemology of psychology Islam as a new scientific study? A series of actions in the framework of realization of the vision described the psychology of Islam as madhhab to five wanted to put a clear identity and firm, without mixed with Western psychology in terms of concept, the study and its methodology.